2005
DOI: 10.1007/bf02731667
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tyndalizedLactobacillus acidophilus in acute diarrhea

Abstract: There is no significant benefit of tyndalized Lactobacillus acidophilus in acute diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…However, lactobacilli also failed to shorten the duration of diarrhoea. At least three randomized controlled trials (RCTs) in developing countries negated the beneficial effect of Lactobacillus GG and L .acidophilus in acute diarrhoea, likely related to the distinct aetiological profile [16,33,50]. In children with more severe diarrhoea, there was no demonstrable benefit of L. casei GG [16,50].…”
Section: Treatment Of Infectious Gastroenteritismentioning
confidence: 96%
“…However, lactobacilli also failed to shorten the duration of diarrhoea. At least three randomized controlled trials (RCTs) in developing countries negated the beneficial effect of Lactobacillus GG and L .acidophilus in acute diarrhoea, likely related to the distinct aetiological profile [16,33,50]. In children with more severe diarrhoea, there was no demonstrable benefit of L. casei GG [16,50].…”
Section: Treatment Of Infectious Gastroenteritismentioning
confidence: 96%
“…Isolaruri et al 1994 (26) observed that the mean duration of diarrheoa was significantly lower in probiotics treated group (1.4 day) compared to yoghurt treated group (2.4 days). While with use of probiotics Billoo et al 2000 (27) , Jobst Henker et al (21) , Enduardo et al (22) Roberto Berni Canani et al (28) and Khanna et al 2000 (23) observed that the mean duration of diarrhoea was 3.6 days, 2.5 days, 58.5 hours, 78.5 hours and 58.78 hours respectively. Similarly Szajewska H. et al 2006; (29) observed that probiotics use were significantly reduced the duration of diarrhoea.…”
Section: Discussionmentioning
confidence: 99%
“…The summary effect size of duration of diarrhea for all included data for probiotics in comparison to placebo in 19 trials [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] was -0.67 with 95% CI= -0.95 to -0.38 (P< 0.0001, Fig. 2a).…”
Section: Duration Of Diarrhea (Day)mentioning
confidence: 99%